Epidemiological profile and presence of IFR6 (rs2235371), TGFA (rs3771494) polymorphisms in individuals with non-syndromic cleft lip and palate - Barajas-Pérez, Víctor Hiram (2022)
Objective. To report the epidemiological profile and the presence of polymorphisms of the IFR6 (rs2235371) and TGFA (rs3771494) genes, in individuals with non-syndromic cleft lip and palate. Methods. Case series study, focused on individuals with orofacial clefts, referred to the School of Dentistry of Durango, Mexico, for review and assessment within the period from January 2018 to December 2019. Information of interest for the study was obtained on the characteristics of pregnancy and family history of the mothers of the individuals. For the analysis and description of the data, the statistical software R Studio was used. Results. There was a higher frequency of men (67%), most of the individuals had the diagnosis of cleft lip and palate at birth (75%), the extension of the complete affection (75%), the left side affected (63%), and corrective surgeries (62%). Only 4% were exposed to maternal smoking (active and passive), 96% had adequate folic acid and iron intake; the risk genotype for TGFA (rs3771494 [G/G]) was present in 15% of cleft lip and 8% of cleft lip and palate, and for IFR6 (rs2235371 [T/T]) only in 10% of cleft lip and palate. Conclusions. The presence of environmental and genetic factors, as well as the maternal lifestyle shown in other populations, may not be the same as those involved in the appearance and development of non-syndromic orofacial clefts in our locality, in addition, the presence of homozygous polymorphic genotypes of the genes of interest could not condition the development of orofacial clefts.